Neuraminidase 1 Exacerbating Aortic Dissection by Governing a Pro-Inflammatory Program in Macrophages - Wang, Qian; Chen, Zhaoyang; Peng, Xiaoping; Zheng, Zeqi; Le, Aiping; Guo, Junjie; Ma, Leilei; Shi, Hongtao; Yao, Kang; Zhang, Shuning; Zheng, Zhenzhong; Zhu, Jianbing (Frontiers in Cardiovascular Medicine, 2021)
Inflammation plays an important role in aortic dissection (AD). Macrophages are critically involved in the inflammation after aortic injury. Neuraminidases are a family of enzymes that catalyze the cleavage of terminal sialic acids from glycoproteins or glycolipids, which is emerging as a regulator of macrophage-associated immune responses. However, the role of neuraminidase 1 (NEU1) in pathological vascular remodeling of AD remains largely unknown. This study sought to characterize the role and identify the potential mechanism of NEU1 in pathological aortic degeneration. After BAPN administration, NEU1 elevated significantly in the lesion zone of the aorta. Global or Macrophage-specific NEU1 knockout (NEU1 CKO) mice had no baseline aortic defects but manifested improved aorta function, and decreased mortality due to aortic rupture. Improved outcomes in NEU1 CKO mice subjected to BAPN treatment were associated with ameliorated vascular inflammation, lowered apoptosis, decreased reactive oxygen species production, mitigated extracellular matrix degradation, and improved M2 macrophage polarization. Furthermore, macrophages sorted from the aorta of NEU1 CKO mice displayed a significant increase of M2 macrophage markers and a marked decrease of M1 macrophage markers compared with the controls. To summarize, the present study demonstrated that macrophage-derived NEU1 is critical for vascular homeostasis. NEU1 exacerbates BAPN-induced pathological vascular remodeling. NEU1 may therefore represent a potential therapeutic target for the treatment of AD.